2016
DOI: 10.1590/s1806-92902016000300005
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance, intestinal morphology, and meat quality in relation to alpha-lipoic acid associated with vitamin C and E in broiler chickens under tropical conditions

Abstract: -This study was conducted to examine the effect of alpha-lipoic acid with vitamin C and E on growth performance, intestinal morphology, and meat quality in broiler chickens under tropical conditions. A total of 288 one-day-old male ROSS 308 chicks (40±0.1 g) were used in a completely randomized design and allotted to one of six dietary treatments to form sixe replicates per treatment (eight birds per cage). The six dietary treatments were: a corn-soybean meal-based diet (NC; no antimicrobial compounds added) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 49 publications
5
11
1
Order By: Relevance
“…During heat exposure, the results of the current study revealed a significant decrease in villus surface area of the small intestine, which was a reflection of a decrease in villus height. Moreover, the VH : CD was lower during heat stress, which again shows that the intestinal environment was unfavourable for the absorption of nutrients owing to the shortening of villus height (Yoo et al, 2016). These findings are in agreement with the results of the authors' previous study (Ashraf et al, 2013) and those of other heat-stress trials conducted in broilers (Silva et al, 2010;Haldar et al, 2011;Song et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…During heat exposure, the results of the current study revealed a significant decrease in villus surface area of the small intestine, which was a reflection of a decrease in villus height. Moreover, the VH : CD was lower during heat stress, which again shows that the intestinal environment was unfavourable for the absorption of nutrients owing to the shortening of villus height (Yoo et al, 2016). These findings are in agreement with the results of the authors' previous study (Ashraf et al, 2013) and those of other heat-stress trials conducted in broilers (Silva et al, 2010;Haldar et al, 2011;Song et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…In broiler production, exposure of bird to heat stress results in economic losses and welfare issues. To achieve optimal production targets, particularly during the summer months, the temperature of the shed must be maintained in a narrow range of 18 °C to 22 °C, which is costly (Yoo et al, 2016). Antibiotics were utilized in the poultry industry to reduce the adverse effects of environmental stress, but their use in animal feed was banned by the EU in 2006 (Skoufos et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in the absorption surface provide a favorable environment for nutrient uptake leading to efficient feed utilization. Several studies have shown the beneficial effects of dietary additives on Ross 308 broiler chicken villus architecture and body weight gain during heat stress challenges such as prebiotic supplements (Silva et al, 2010), alpha-lipoic acid additive (Yoo et al, 2016), or probiotic mixtures (Song et al, 2014). Similarly, the data presented here suggests that nutrient absorption competence associated with the development of villi in the small intestine of birds fed the GOS diet, leads to an increase in body weight despite gut colonization by C. jejuni.…”
Section: Discussionsupporting
confidence: 66%
“…On the contrary, Elsayed et al (2009) who found that TC of local chicken eggs at 39.5to 40.5°C for 3h/d at 15-17 day of incubation, resulted in a significant increase in plasma total proteins level. Moreover, the significant increase in plasma TP level by vitamin C addition is in close agreement with many results which showed that the addition of vitamin C to the drinking water could significantly reduce the physiological stress and hence improve the biochemical parameters of blood (Pardue and Thaxton., 1986); (Kutlu and forbes., 1993a,b); ( Konce, et al, 2009); ( Imik, et al, 2013) and (Yoo,et al, 2016). P˂0.05).…”
Section: Plasma Total Proteins (Tp Alb and Globulin)mentioning
confidence: 96%